GluN2A or GluN2B subunits of the NMDA receptor contribute to changes in neuronal excitability and impairments in LTP in the hippocampus of aging mice but do not mediate detrimental effects of oligomeric Aβ (1–42) - Südkamp, Nicolina; Shchyglo, Olena; Manahan-Vaughan, Denise (Frontiers in Aging Neuroscience, 2024)
Studies in rodent models have revealed that oligomeric beta-amyloid protein [Aβ (1–42)] plays an important role in the pathogenesis of Alzheimer’s disease. Early elevations in hippocampal neuronal excitability caused by Aβ (1–42) have been proposed to be mediated via enhanced activation of GluN2B-containing N-methyl-D-aspartate receptors (NMDAR). To what extent GluN2A or GluN2B-containing NMDAR contribute to Aβ (1–42)-mediated impairments of hippocampal function in advanced rodent age is unclear. Here, we assessed hippocampal long-term potentiation (LTP) and neuronal responses 4–5 weeks after bilateral intracerebral inoculation of 8–15 month old GluN2A+/− or GluN2B+/− transgenic mice with oligomeric Aβ (1–42), or control peptide. Whole-cell patch-clamp recordings in CA1 pyramidal neurons revealed a more positive resting membrane potential and increased total spike time in GluN2A+/−, but not GluN2B+/−-hippocampi following treatment with Aβ (1–42) compared to controls. Action potential 20%-width was increased, and the descending slope was reduced, in Aβ–treated GluN2A+/−, but not GluN2B+/− hippocampi. Sag ratio was increased in Aβ–treated GluN2B+/−-mice. Firing frequency was unchanged in wt, GluN2A+/−, and GluN2B+/−hippocampi after Aβ–treatment. Effects were not significantly different from responses detected under the same conditions in wt littermates, however. LTP that lasted for over 2 h in wt hippocampal slices was significantly reduced in GluN2A+/− and was impaired for 15 min in GluN2B+/−-hippocampi compared to wt littermates. Furthermore, LTP (>2 h) was significantly impaired in Aβ–treated hippocampi of wt littermates compared to wt treated with control peptide. LTP induced in Aβ–treated GluN2A+/− and GluN2B+/−-hippocampi was equivalent to LTP in control peptide-treated transgenic and Aβ–treated wt animals. Taken together, our data indicate that knockdown of GluN2A subunits subtly alters membrane properties of hippocampal neurons and reduces the magnitude of LTP. GluN2B knockdown reduces the early phase of LTP but leaves later phases intact. Aβ (1–42)-treatment slightly exacerbates changes in action potential properties in GluN2A+/−-mice. However, the vulnerability of the aging hippocampus to Aβ–mediated impairments of LTP is not mediated by GluN2A or GluN2B-containing NMDAR.